Book Review: Epistemic Cognition and Development: The Psychology of Justification and Truth - Anindito Aditomo (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2017)
Although relatively unpopular among Indonesian scholars, the study of epistemic cognition has emerged as a major area of research at the intersection of psychology and education. A number of edited books and special editions in respected journals have been dedicated to various issues related to epistemic cognition. However, David Moshman’s “Epistemic Cognition and Development” (henceforth, ECD) is the first textbook which provides a comprehensive introduction to theories and research on epistemic cognition. With this book, Moshman deserves much credit for providing not only valuable insights on a number of key conceptual issues, but also situating those insights within the broader picture of cognitive and developmental theories.